Institutional Innovations and Adaptive Behaviour in the Russian Education - Vera V. Kot (Ural State University of Economics, 2018)
The paper contains the results of the study of further vocational education in Rostov oblast conducted by the Economic Faculty’s staff of the South Federal University in 2015–2017. The article focuses on institutional innovations in the Russian education which transform primarily formal institutions. These innovations take place in the areas of content-related modernization of education, development and implementation of new educational technologies and training methods, creation of new types of educational institutions, as well as in the areas of upbringing, training, retraining and management in education. The authors emphasize that institutional innovations are not necessarily lead to creation of effective institutions. For instance, in the field of higher education institutional innovations transform the educational paradigm increasing its formalization and providing extra opportunities for regulation. The article analyses institutional innovations in the context of adaptive behaviour of the main actors of the higher and further vocational education system at the state and organizations level. The conducted qualitative studies of institutional innovations in this sphere allow us to outline the results of the implemented educational innovations and put forward suggestions on reducing negative effects of institutional changes. The obtained results can be useful to researchers in the field of institutional economics, economics of education, and when designing government programmes for higher education development.